School coexistence to improve learnin. - López Páez, Hugo Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This article provides some information about the classroom Project that was developed at educational institution San Isidro. The objective is stren- gthening shared school environment in students at second, third and fifth grades of the San Isidro educational institution of the municipality of Umbita. In order to improve the learning process. This study employed a descriptive research method. The situation of coexistence in the class- room were determined. Furthermore, surveys, workshops with students and parents were also carried out. The results show that shared school environment isn’t the best. It can be concluded that parents’ interaction in the learning process is fundamental. For that reason parents at home must instill values to their children ever since early years of children’s life.